Language Management and Resource Governance: A Panacea for Curbing Youth Restiveness in the Niger Delta Region (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The study investigated the role of language management and resource governance in mitigating youth restiveness in the Niger Delta region of Nigeria. The region, encompassing nine States, namely Abia, Akwa Ibom, Bayelsa, Cross River, Delta, Edo, Imo, Ondo, and Rivers, faces challenges despite its rich natural resources, including oil and gas. These challenges include environmental degradation, poverty, and widespread youth restiveness. This work focused on six States from the South-South geopolitical zone made up of Bayelsa, Rivers, Akwa Ibom, Cross River, Edo and Delta. A survey research design was employed, involving 1,105 male and female youths, to explore opinions on language's role in conflict resolution and the impact on resource governance practices. Data was collected using questionnaires and analyzed using descriptive statistics and Chi-square tests and the analysis confirms significant associations between effective language use, resource governance, and decreased incidents of youth restiveness. Findings indicated widespread support for language as a tool for conflict resolution and emphasized the importance of transparent and inclusive resource governance in addressing youth restiveness. The study recommends involving youths in decision-making and utilizing inclusive, respectful language to address grievances, policy interventions that prioritize effective communication strategies and equitable resource distribution to promote social harmony and reduce tensions in the Niger Delta.